2016
DOI: 10.1007/s00701-016-2805-5
|View full text |Cite
|
Sign up to set email alerts
|

Transient disappearance of microbleeds in the subacute period based on T2*-weighted gradient echo imaging in traumatic brain injury

Abstract: We report three cases of traumatic microbleeds evaluated by sequential observation. Hypo-intensities on T2* gradient echo imaging (T2*GEI) appeared just 2-3 h after the injury (the hyper-acute period). However, these hypo-intensities on T2*GEI disappeared or became obscure 2-6 days after the injury (the subacute period). A follow-up MRI again revealed clear hypo-intensities on T2*GEI 1-3 months after the injury (the chronic period). Our cases indicate that hypo-intensities on T2*GEI might change dynamically fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…This observation remains to be replicated in other domains and larger-scale studies, yet it indicates that MR imaging should ideally be performed early after mild traumatic brain injury, notably because the detection rate of nonhemorrhagic diffuse axonal injury features (eg, areas of diffusion restriction) is also higher in the immediate posttraumatic period. Moreover, intriguing recent reports indicate that CMBs may show dynamic changes after the acute injury, including growth (80) and temporary disappearance (81). These reports further support that the timing of imaging is important, but this needs confirmation in future studies.…”
Section: Traumatic Brain Injurymentioning
confidence: 66%
“…This observation remains to be replicated in other domains and larger-scale studies, yet it indicates that MR imaging should ideally be performed early after mild traumatic brain injury, notably because the detection rate of nonhemorrhagic diffuse axonal injury features (eg, areas of diffusion restriction) is also higher in the immediate posttraumatic period. Moreover, intriguing recent reports indicate that CMBs may show dynamic changes after the acute injury, including growth (80) and temporary disappearance (81). These reports further support that the timing of imaging is important, but this needs confirmation in future studies.…”
Section: Traumatic Brain Injurymentioning
confidence: 66%
“…Similar changes in CMB volume have previously been reported during the acute and chronic phases following a traumatic brain injury. [24][25][26] Liu et al found a dramatic decrease in quantitative measures of CMBs from serial imaging acquired beyond 2 years postinjury, 24 while Lawrence et al and Watanabe et al reported the appearance of CMBs within the first few hours following injury; CMBs showed reductions in volume over a 2-15-day period that were associated with patient recovery. 25,26 Thus, identifying treatment strategies to accelerate the mechanism through which CMBs decrease in size may be a viable alternative for minimizing CMBassociated deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent preliminary studies have highlighted the potential for detection of TCMBs in the first few days after injury [18] [19] . The modest number of patients recruited provided only preliminary indication of a link between TCMB severity and clinical outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies suggested that lesions could be identified, and will evolve, in the first week following trauma. One study suggested an increase in lesion volume and an apparent reduction in number due to lesion coalescence [18] ; the other showed a reduction in lesion volume in the same timeframe [19] . The authors of the first study suggested that an increase in lesion volume could be explained by progressive microvascular damage.…”
Section: Introductionmentioning
confidence: 99%